Implementation of Network Security Using Intrusion Prevention System (IPS) with Telegram Based Notification at PT Cyber Access Indonesia - Apriana, Gede Angga; Piarsa, I Nyoman (Jurnal Ilmiah Merpati (Menara Penelitian Akademika Teknologi Informasi), 2025)
Network security is a crucial aspect for information technology-based companies such as PT Cyber Akses Indonesia. Security threats such as brute force attacks, malware, and DDoS are increasingly common. One proposed solution is the implementation of an Intrusion Prevention System (IPS), which functions to detect and prevent suspicious attacks while providing Telegram-based notifications. The methodology used is the Network Development Life Cycle (NDLC), covering stages from analysis to management. The results of the testing show that the IPS security configuration on MikroTik is capable of identifying and blocking attacks based on threat levels. The real-time notification system via Telegram Bot greatly assists administrators in responding more quickly. Quality of Service (QoS) analysis also indicates that the implementation of IPS security does not significantly degrade network performance, with an average QoS score of 3,5 across tested parameters such as throughput, packet loss, delay, and jitter.